An initial investigation into the application of surfactin, a biosurfactant, as an alternative desulphurisation agent, for the prevention of acid mine drainage, via froth flotation - Augustyn, Andre Rossouw (Stellenbosch : Stellenbosch University, 2020)
Thesis (MEng)--Stellenbosch University, 2020.